The dynamic effects of barometric forcing on storm-surges in the Bay of Bengal (MAUSAM, 1980)
The numerical model developed by Johns and Ali (1980a) has been used to study the dynamc contribution of atmospheric pressure anomaly on storm surges in the Bay of Bengal. The contribution due to this factor has also been compared with that due to wind-stress alone. It is found that dynamic effects of barometric forcing can to a reasonable approximation be represented by a statical corrections.